Cultural Truth and Ethnographic Consequences - Levin, Michael (Culture, 1991)
Fieldwork in an increasingly literate world presents new dilemmas for anthropologists. The information recorded in ethnographies may have consequences in the cultures and for the people with whom the ethnographer has worked. The political system of the peoples′ nation may be able to use ethnographic information and the politics of the local community can be affected by the permanent record an ethnography creates. This paper uses an old baseball story as a metaphor for the decisive powers of the ethnographer, and illustrates the issues with four instances calling for decisions from fieldwork in southeastern Nigeria.